2004
DOI: 10.1016/s1053-8119(04)00370-2
|View full text |Cite
|
Sign up to set email alerts
|

How does the brain accommodate to increased task difficulty in word finding?A functional MRI study

Abstract: In functional imaging of the brain, the difficulty of a task may be critical for the pattern of activation. Increased task difficulty could lead to increased activation in task-specific regions or to activation of additional, "compensatory" regions. A previous study with functional transcranial Doppler sonography (fTCD) showed no evidence that increased difficulty in word retrieval leads to a recruitment of areas homologous to language-related regions. The question remains how the brain accommodates increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…This effect concerned regions normally activated by word generation tasks, ie, superior temporal gyri and left inferior frontal cortex, 17 as well as regions located upwards (superior parietal lobule, middle, and superior frontal gyri) that may reflect earlier compensatory phenomena in the most effective patients. 18 It should be noted that although very contrasted in anatomical terms, the 2 described patterns shared a common region located in the anterior part of the left inferior temporal gyrus (Figure 2) whose functional significance is discussed here.…”
Section: De Boissezon Et Al Subcortical Aphasia 1471mentioning
confidence: 77%
“…This effect concerned regions normally activated by word generation tasks, ie, superior temporal gyri and left inferior frontal cortex, 17 as well as regions located upwards (superior parietal lobule, middle, and superior frontal gyri) that may reflect earlier compensatory phenomena in the most effective patients. 18 It should be noted that although very contrasted in anatomical terms, the 2 described patterns shared a common region located in the anterior part of the left inferior temporal gyrus (Figure 2) whose functional significance is discussed here.…”
Section: De Boissezon Et Al Subcortical Aphasia 1471mentioning
confidence: 77%
“…Theoretically, compensatory strategies used by children with ADHD depends on many factors, including the nature and difficulty of the task paradigm (Drager et al 2004) and the RI capacity of the children (Hoeft et al 2007), which is known to be lower in children with ADHD than in unaffected children (Swanson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown that increasing task difficulty leads to recruitment of language homologue areas in the right hemisphere [Just et al, 1996;St George et al, 1999; see also Dräger et al, 2004 who did not confirmed these results]. However, task accuracy was similar during word repetition for AD and control participants, a finding that is not consistent with an interpretation in terms of group-related differences in task difficulty; rather, abnormal activation in the right superior temporal gyrus, in conjunction with preserved levels of performance for repeating words, may be interpreted as reflecting the recruitment of alternative, compensatory lexicosemantic networks during word repetition.…”
Section: Cortical Activation For Lexicosemantic Representations In Admentioning
confidence: 99%